Biodiversity of urban green spaces and human health: a systematic review of recent research - Chia-Ching Wu; Joy O’Keefe; Yizhen Ding; William C. Sullivan; William C. Sullivan (Frontiers in Ecology and Evolution)
Although recent studies have explored links between landscape biodiversity and human health, the exact effects of specific types of biodiversity—such as the variety of species or genera—on health outcomes are still uncertain. In this review, we evaluate our current knowledge of how landscape biodiversity influences human health in different cultural contexts. We systematically assessed peer-reviewed literature to: 1) summarize the links between biodiversity variability and human health outcomes; 2) describe the pathways used to examine these links; 3) compare subjective perceptions of biodiversity with objective measures; and 4) describe any known connections between perceived biodiversity and health outcomes. We analyzed 41 studies published between 2018 and 2023, covering research from 15 countries on five continents. A key finding was the lack of significant links between biodiversity variability, like species richness, and health outcomes; only one-third of studies reported positive health effects. We identified two main pathways: restoring health capacities (mental health) and building health capacities (physical health). The public could identify different biodiversity levels, with perceived biodiversity correlating with health. Future research should explore varied mechanisms, physical health outcomes, causal relationships, and effects across diverse populations and regions.